Complex network analysis of slaughterhouse waste anaerobic digestion: From failure to success of long-term operation. (October 2022) - Dalantai, Tergel; Rhee, Chaeyoung; Kim, Dae Wook; Yu, Sung Il; Shin, Juhee; Triolo, Jin Mi; Shin, Seung Gu
Graphical abstract: Highlights: Solid-state digestion experienced operation instability due to ammonia inhibition. Liquid-state digestion showed stable biogas production at 2 gVS L −1 d. Tissierellaceae contributes to the early stage of slaughterhouse waste digestion. Hydrogenotrophic methanogens had higher tolerance to FAN than other methanogens. Complex network patterns differ depending on the stability of anaerobic digester. Abstract: The study explored slaughterhouse waste (SHW) as prime feedstock associated with and without supplement of an external slowly degradable lignocellulosic carbon source to overcome the synergistic co-inhibitions of ammonia and fatty acids. Long-term solid-state digestion (SSD) and liquid-state digestion (LSD) were investigated using a mixture of pork liver and fat. At 2.0 g volatile solids (VS) L −1 d −1 of organic loading rate (OLR), the two reactors of SSD experienced operational instability due to ammonia inhibition and volatile fatty acid (VFA) accumulation while LSD successfully produced 0.725 CH4 L CH4 g −1 VS during 197 d of working days under unfavorable condition with high total ammonia nitrogen (>4.7 g/L) and VFAs concentration (>1.9 g/L). The network analysis between complex microflora and operational parameters provided an insight for sustainable biogas production using SHW. Among all, hydrogenotrophic methanogens have shown better resistance than acetoclastic methanogens.